The Analisis Retail Service, Customer Experience, Switching Barriers, Kepuasan Konsumen Terhadap Loyalitas Konsumen UMKM Ritel - Fatimah, Feti; Murtalining Tyas, Wenny; Sukma Hadi, Nadia (Institut Teknologi dan Sains Mandala, 2024)
Malls and modern retail stores established in Jember Regency are connected to each other even though they are close together, causing problems for SMEs engaged in the retail business. Therefore, it is necessary to explore how to make consumers loyal to retail SMEs by introducing retail services, changing barriers through customer experience and consumer satisfaction, so that retail SMEs can continue to exist and develop. The aim of this research is to determine the barriers to consumer loyalty through customer experiences with retail services and consumer satisfaction in retail MSMEs located in Jember Regency. The design of this research is confirmatory research and at the same time explanatory research. The research population is all buyers from MSME retail companies in Jember Regency. Standardization of Retail MSMEs that sell daily needs and the mini market concept. The research sample was taken using non-probability sampling technique using purposive sampling and random sampling. The sample size of this research is 225 respondents. The data analysis method used in this study is; descriptive statistical analysis and structural equation modeling (SEM) using SEM-PLS. The results of the research are: Retail services have no effect on consumer satisfaction, customer experience has an effect on consumer satisfaction. Barriers to change affect consumer satisfaction. Retail services influence consumer loyalty. Customer experience influences consumer loyalty. Switching barriers do not affect consumer loyalty. Consumer satisfaction influences consumer loyalty. Retail services have no effect on consumer loyalty through consumer satisfaction. Customer experience influences consumer loyalty through customer satisfaction. Switching barriers does not affect consumer loyalty through consumer satisfaction.